Anthropogenic Modifications Can Significantly Influence the Local Mean Sea Level and Affect the Survival of Salt Marshes in Shallow Tidal Systems. Issue 5 (11th May 2018) - Silvestri, Sonia; D'Alpaos, Andrea; Nordio, Giovanna; Carniello, Luca
Abstract: In a shallow dissipative tidal system, interventions that modify the local morphology in one location of the basin may quickly affect the surrounding areas, promoting strong changes in their morphology. If the localized modification persists over time, it may produce far‐field morphological modifications at delayed times. These modifications may have an impact on the local mean sea level and on tidal range, affecting the fate of salt marshes with implications for their survival. In this study, we investigate the effect of two anthropic interventions performed between the end of the nineteenth century and the beginning of the twentieth century in the northern Venice lagoon (Italy): the construction of jetties at one inlet and the removal of reed barriers protecting a fish farm in the inner lagoon. Using a 2‐D numerical model to reproduce the hydrodynamics of different historical lagoon configurations and a zero dimensional model of marsh vertical accretion, we investigate the effect of these interventions on the salt marshes of the northern lagoon basin. Interestingly, our results show that the increased depth at the inlet induced by the jetties lowered the local mean sea level of nearby areas and increased the tidal range, producing a temporary positive feedback on the stability of the marshes in proximity of the inlet. On the contrary, in the inner lagoon areas characterized by extremely low marshes, the removal of reed barriers delimiting a fish farm may have reduced the sediment fluxes thus contributing to the drowning of large marsh surfaces. Key Points: A modified hydrodynamics at a lagoon inlet may temporarily slow down the local sea level rise facilitating the survival of nearby salt marshes In shallow dissipative microtidal systems, the extremely small tidal amplitude of the inner areas is a risk factor for the marsh survival in response to decreased sediment inputs Human interventions performed in one location of a coastal lagoon may produce deep far‐field modifications of the morphology at delayed times